Correlation analysis on the Specific Absorption Rate (SAR) between metallic spectacle and pins exposed from radiation sources - Mohd Hafizuddin, Mat; Mohd. Fareq, Abd. Malek, Dr.; Syed Idris, Syed Hassan, Prof. Dr.; Muhammad Solihin, Zulkifli; Ronald, Suzanna Harun (The Electromagnetics Academy, 2013)
Link to publisher's homepage at http://emacademy.org/